Ethical Standards for Stockbrokers: Fiduciary or Suitability? - Angel, James Joseph; MacCabe, Douglas M. (2013)
What are the ethical obligations of the sellers of financial products to their customers? Stockbrokers in the U.S. have a legal and ethical requirement to recommend only “suitable” investments to their customers. This is a fairly weak standard. Currently, there are proposals to raise the standard to a fiduciary one in which the recommendations would have to be in the best interests of the clients. Brokers sell solutions to financial problems. Similar to an auto mechanic or a doctor, the product often consists of both the professional advice and its implementation. There are numerous conflicts of interest between brokerage firms and their customers in that the products that pay the highest commissions may not be the best ones for the customers. The societal perspective adds complications, however. Society depends on modern financial markets to raise capital for productive enterprises and to spread risk. Issuers of financial products need distribution channels for their products just like the producers of any other products. Commissions create powerful incentives for the distribution channels, but at the same time produce conflicts of interest—a type of ethical pollution. Just as our society tolerates some pollution as a byproduct of other useful activities, it may be useful to tolerate some of these financial conflicts of interest. The nature of the relationship should govern the ethical standard. Those selling advice, regardless of how they label themselves, should adhere to a best-interest fiduciary standard. More limited relationships should be limited to the mandate involved in the relationship.
Keywords: Ethical standards; Stockbrokers; Fiduciary; Suitability; Financial services